The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.numecd.2021.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the degree of adherence to the mediterranean diet and its components on cardiometabolic risk during pregnancy. The GESTAFIT project

Abstract: Background and aims: Studies regarding dietary patterns and cardiometabolic risk markers during pregnancy are scarce. The aim of the present study was to analyse whether different degrees of adherence to the Mediterranean diet (MD) and the MD components were associated with cardiometabolic markers and a clustered cardiometabolic risk during pregnancy. Methods and results: This study comprised 119 pregnant women from the GEStation and FITness (GESTAFIT) project. Dietary habits were assessed with a food frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…with a food frequency questionnaire previously evaluated for validity in the Spanish nonpregnant adult population (Mataix et al, 2000). By means of the data obtained from the food frequency questionnaire, the Mediterranean Diet Score (Panagiotakos et al, 2006) was employed to assess MD adherence as previously done in this study sample (Flor‐Alemany et al, 2021). The Mediterranean Diet Score (Panagiotakos et al, 2006) consists of 11 variables (i.e., whole grain cereals, potatoes, fruits, vegetables, pulses, fish, olive oil, red wine, red meat and subproducts, poultry and whole dairy products) ranging from 0 to 5 according to their position in the MD pyramid (Bach‐Faig et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…with a food frequency questionnaire previously evaluated for validity in the Spanish nonpregnant adult population (Mataix et al, 2000). By means of the data obtained from the food frequency questionnaire, the Mediterranean Diet Score (Panagiotakos et al, 2006) was employed to assess MD adherence as previously done in this study sample (Flor‐Alemany et al, 2021). The Mediterranean Diet Score (Panagiotakos et al, 2006) consists of 11 variables (i.e., whole grain cereals, potatoes, fruits, vegetables, pulses, fish, olive oil, red wine, red meat and subproducts, poultry and whole dairy products) ranging from 0 to 5 according to their position in the MD pyramid (Bach‐Faig et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…After considering relevant confounders suggested by the previous literature, Model I was unadjusted and Model II was adjusted for BMI and the adherence to the Mediterranean dietary pattern. 24,26,27 Since other variables according to the literature showed a weak relationship or no relationship with the studied outcomes (eg, marital status and hormonal therapy), these variables were only tested as additional confounders in secondary sensitive analyses (data not shown). The Benjamini-Hochberg procedure was applied to account for the random effect in multiple comparisons for all the tests included in the analysis with q ¼ 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Menopause- related symptoms were included in the regressions as dependent variables and the group (counseling or exercise) as the independent variable. After considering relevant confounders suggested by the previous literature, Model I was unadjusted and Model II was adjusted for BMI and the adherence to the Mediterranean dietary pattern 24,26,27 . Since other variables according to the literature showed a weak relationship or no relationship with the studied outcomes (eg, marital status and hormonal therapy), these variables were only tested as additional confounders in secondary sensitive analyses (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…Diet significantly contributes to increasing the pregnancy risk from early gestation [ 8 ], playing a key role in the regulation of chronic inflammation in pregnant and non-pregnant adults [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. In fact, several high-quality studies, reviews, and meta-analyses have demonstrated that the Mediterranean diet (MD) is a healthy dietary pattern and that higher adherence to MD is associated with the prevention of several diseases and lower inflammatory levels [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%